Music Training, Working Memory, and Neural Oscillations: A Review - Yurgil, Kate A.; Velasquez, Miguel A.; Winston, Jenna L.; Reichman, Noah B.; Colombo, Paul J. (Frontiers in Psychology, 2020)
This review is focused on reports that link music training to working memory and neural oscillations. Music training is increasingly associated with improvement in working memory, which is strongly related to both localized and distributed patterns of neural oscillations. Importantly, there is a small but growing number of reports of relationships between music training, working memory, and neural oscillations in adults. Taken together, these studies make important contributions to our understanding of the neural mechanisms that support effects of music training on behavioral measures of executive functions. In addition, they reveal gaps in our knowledge that hold promise for further investigation. The current review is divided into the main sections that follow: 1) Discussion of behavioral measures of working memory, and effects of music training on working memory in adults; 2) Relationships between music training and neural oscillations during temporal stages of working memory; 3) Relationships between music training and working memory in children; 4) Relationships between music training and working memory in older adults; and 5) Effects of entrainment of neural oscillations on cognitive processing. We conclude that the study of neural oscillations is proving useful in elucidating the neural mechanisms of relationships between music training and the temporal stages of working memory. Moreover, a lifespan approach to these studies will likely reveal strategies to improve and maintain executive function during development and aging.